Analysis of robot as a substitute for barista using Thomas Kuhn's paradigm theory approach: barista robot at Family Mart store - Diana, Marselin; Kuswanti, Ana; Mulyana, Ahmad (Gema Wiralodra, 2023)
Technological developments have created many innovations that help make human life more manageable. One of these developments is the Bariska Robot presented at the Family Mart Grand Indonesia Store, Jakarta. Even though its existence is welcomed, quite a few feel that it is a threat to humans because it is considered that it can replace the role of the Barista. The presence of robot baristas cannot replace the baristas themselves. Baristas have values ​​that apparently cannot be imitated by robots. In this research, the author used the library research method to collect information according to the needs of this research. As well as using Thomas S. Kuhn's ideas to examine the role of paradigms in the scientific revolution. Which is the basis of the technological changes that occur.